Nano- and micro-mechanics of polymer blends and composites - Karger-Kocsis, J.; Fakirov, Stoyko (Hanser, 2009)
"The aim of this book is to give a state-of-art overview on aspects of micro- and nanomechanics of polymers, polymeric blends and composites"--Provided by publisher.